A Comprehensive Assessment of Auto-Enrollment System as a Second Pillar of Pension System: The Case of Turkey - Kayhan, Fatih; Islamoglu, Mehmet (International Journal of Publication and Social Studies, 2020)
The aim of this study is to provide an overview of Auto-Enrollment System (AES) in Turkey; and also to examine impact of Covid-19 upon the development of number of participants and contribution amounts. AES is considered as the second-pillar of pension system. In this study, data is retrieved from official website of Turkish Pension Monitoring Authority (EGM) and Turkish Electronic Fund Trading Platform (TEFAS). The method utilized in this paper is SWOT analysis. This is the first study in Turkey to explain daily pension fund operations together with the impact of pandemic on the AES branch of insurance business. This study argues that auto-enrollment system in Turkey has high growth potential and this system is expected to reach a statistically significant asset level in terms of total asset under management in the medium and long term. This study also indicates that as of the end of September 2020, AES in Turkey was not significantly affected by the coronavirus pandemic (Covid-19) in regard to number of participants and contribution amount in local currency-.